Design criteria of subway tunnels - Ghiasi, Vahed; Omar, Husaini; Md Yusoff, Zainuddin; Kim Huat, Bujang; Muniandy, Ratnasamy; Ghosni, Nassin; Nushini, Amin; Afshar, Mohhamad Amin; Ghiasi, Samad; Hosaini, Seyeg Ghavamodin; Ghiasi, Mohammad (American-Eurasian Network for Scientific Information, 2010)
This paper is dedicated to present criteria and rules for design of metro path including tunnel geometrical sections and choosing parameters, loads applied to tunnels, fundamentals of static and seismic analysis, and primaries of structural design, structural joints, and control criteria, behavior measuring and sensitive devices. Design criteria of shallow and semi-deep tunnels are presented in this paper.